Analysis of Students' Proficiency in Mathematical Communication Through the View of Self-Regulated Learning - Sari, Fitri Aida; Kusumah, Yaya Sukjaya; Juandi, Dadang (Mathematics Dept, Math. and Science Faculty, Universitas Negeri Semarang, 2023)
Changes in the education implementation system during the Covid-19 pandemic force students to adapt quickly. This adaptation occurs because online learning limits teachers ' ability to monitor the overall learning carried out by students. Therefore, in the implementation, students must have Self-Regulated Learning to manage their learning activities independently and analyze their learning needs. In addition, Self-Regulated Learning is also able to provide support for improving various abilities, for example, mathematical communication. This study aimed to determine whether Self-Regulated Learning affects students’ mathematical communication skills. The research method used is correlational with a sample of 31 students in grade IX of a junior high school in Serang City. The results of this study indicate that Self-Regulated Learning affects students' mathematical communication skills, with a coefficient of determination equal to 21%. This research can inform educators that Self-Regulated Learning influences students' mathematical communication abilities, so educators must design learning to help improve students' Self-Regulated Learning.Perubahan sistem pelaksanaan pendidikan pada kondisi pandemi Covid-19 memaksa siswa untuk beradaptasi secara cepat. Adaptasi tersebut terjadi karena pembelajaran secara online memberikan batasan bagi guru untuk memantau keseluruhan pembelajaran yang dilakukan oleh siswa. Oleh karena itu, dalam pelaksanaan pembelajaran secara online siswa harus memiliki Self-Regulated Learning agar mampu mengatur kegiatan belajarnya secara mandiri dan mampu menganalisis kebutuhan belajarnya. Selain memberi dukungan yang besar terhadap pelaksanaan pembelajaran secara online, Self-Regulated Learning juga mampu memberikan dukungan terhadap peningkatan berbagai kemampuan, salah satunya adalah komunikasi matematis. Penelitian ini bertujuan untuk mengetahui apakah terdapat pengaruh Self-Regulated Learning terhadap kemampuan komunikasi matematis siswa. Metode korelasional digunakan dengan sampel penelitian sebanyak 31 murid kelas IX di salah satu SMP di Kota Serang. Hasil penelitian ini menunjukkan Self-Regulated Learning berpengaruh terhadap kemampuan komunikasi matematis siswa dengan koefisien determinasi yaitu sebesar 21%. Penelitian ini dapat memberikan informasi kepada pendidik bahwa Self-Regulated Learning berpengaruh terhadap kemampuan komunikasi matematis siswa, sehingga pendidik harus merancang pembelajaran yang dapat membantu meningkatkan Self-Regulated Learning siswa.